Trade logistics and regional integration in Latin America and the Caribbean - Pablo Guerrero; Krista Lucenti; Sebastián Galarza (Asian Development Bank Institute (ADBI), 2010)
During the past few decades, the landscape of the world economy has changed. New trade patterns reflect the globalization of the supply chain and intra-industry trade, and increasing flows between neighboring countries and trading blocs with similar factor endowments. Similarly, the approach to production, trade, and transportation has evolved incorporating freight logistics as an important value-added service in global production. This integrated approach have become essential, and as such, both the trade agenda and freight logistics are beginning to converge providing an unparalleled opportunity for countries to deepen their integration with neighboring countries and their national performance in transport related services. Consequently, developing countries are finding themselves hard-pressed to adjust their policy agendas to take into account costs not covered in past rounds of trade negotiations. This paper focuses on the importance of freight logistics in trade facilitation measures, examines the transport and logistics cost in international trade, addresses logistics performance in Latin America and the Caribbean and regional initiatives to advance the integration process and finally, exchanges views on the potential for trade logistics to impact the regional agenda and to deepen integration.
Keywords: F15; 330; Transportlogistik; Transportkosten; Handelsregionalismus; Karibische Staaten; Lateinamerika